PS-030 Impact of electronic prescribing on the quality and safety of chemotherapy prescribing in oncology and haematology. (25th February 2017) - Murphy, D; Ryan, B; O'Donovan, M; Dooley, G; Burgess, A; Ging, P; Meegan, C
Abstract : Background: In July 2015, the electronic software CATO was introduced for chemotherapy prescribing. Before CATO implementation, chemotherapy prescriptions were handwritten on a designated form. Purpose: To determine the impact of electronic prescribing by comparing the rate of prescribing errors and omissions using handwritten versus electronic prescriptions, and to compare the clinical significance of errors and omissions for both prescribing methods. Material and methods: A data collection form was designed based on chemotherapy prescription requirements detailed by the National Cancer Control Programme (NCCP) in Ireland. Omissions and errors were defined as the absence or incorrect recording of these requirements. Data collection was completed by 4 pharmacists. Pharmacists categorised prescription errors/omissions as potentially clinically significant or not. This was not graded for this analysis. A pilot (n=30) was completed by all data collectors to ensure consistent data collection. Only parenteral oncology/haematology prescriptions were included. Data were collected in two phases. Phase 1 was a retrospective review of handwritten chemotherapy prescriptions identified by random systematic sampling. Phase 2 was a prospective analysis of electronic prescriptions. A sample size with 60% population proportion was chosen. Results: 153 handwritten prescriptions and 153 electronic prescriptions were analysed. 53% reduction in prescribing errors was found (p<0.05). At least 1 error was found in 29% of handwritten prescriptions (range 1–4) compared with 14% of electronic prescriptions (range 1–2). The mean number of omissions found per handwritten prescription was 3 (range 1–6) compared with 0 for electronic prescriptions (range 0–1) (p <0.05). Electronic prescribing reduced the incidence of errors/omissions considered potentially clinically significant from 17% to 6% (p <0.05). Examples of these included incorrect doses and chemotherapy or supportive care omissions. Common errors encountered with handwritten prescriptions were incorrect body surface area and cycle number. Common errors associated with electronic prescriptions were incorrect dose reductions and incorrect date of treatment. Conclusion: Introduction of CATO prescribing has significantly reduced prescribing errors. Potentially clinically significant errors and omissions have also greatly reduced. These data, although subjective, suggest that the quality and safety of chemotherapy prescribing has greatly improved. Continued auditing of prescribing errors and omissions is imperative to further improve these results. No conflict of interest